The Transfer of European Educational Practices into the Russian Empire in the 19th Century: The Main Channels and Elite Reflections - But, Yulia (Quaestio Rossica, 2019)
This article considers the transfer of European educational patterns into Russia. The author demonstrates that they became a primary point of reference for Russian elites as early as the 18th century. In the 19th century, however, the transfer of European educational experience to Russia considerably increased and acquired new features, drawing in wide circles of Russian educational elites who were critical of the structures, methods, and ideals they were adopting from abroad. By this time, the political elites of Russia had already adopted the European idea of schooling as one of the most important channels for propagandising the national idea at each educational level: this meant the sustained involvement of the Russian state in the development of the education system. The article identifies and characterises the main channels through which European educational practices were transferred into the Russian Empire in the 19th century and studies the reflections of Russian educational elites on the process. The study is based on the reports of officials, the accounts of inspections of various educational institutions, the reports of university professors and gymnasium teachers on their academic missions abroad, and the publications of renowned Russian teachers analysing European educational achievements and their possible application in Russia. The study makes it possible to identify a number of channels through which European educational practices were transferred into Russia in the 19th century, i. e. schools of the European type, foreign boarding schools in the central Russian provinces, Russian seminars at leading European universities, and the so-called “pedagogical journeys” of the educated elite. The two latter channels were found to be the most efficient and desirable for the government. The transfer of foreign educational experience into Russia throughout the 19th century is represented in the study as a process on which Russian elites deeply reflected: they sought to bring the Russian schooling system in line with developed European patterns in the most appropriate way.